TEROR SUCI: KEKERASAN ATAS NAMA AGAMA - Abdul Muis Naharong (Universitas Paramadina, 2013)
AbstractSince the last few decades there have been a lot of discussions on the role ofreligion in promoting acts of violence considered as terrorism. This is due tothe fact that many of the perpetrators of these acts claimed that their acts ofviolence were committed in the name of God. They acted as the soldiers ofGod who were punishing wayward leaders who did not implement God’sLaws or exacting vengeance on people who were violating their honor or/andmassacring their fellow coreligionists. Several scholars, however, claim thatreligion does not have anything to do with violence or terrorism. In theirviews religion is innocent and victim of a few radicals who use and abusereligion to further their non-religious interests. Several others do believethat religion has something to do with acts of violence deemed as terrorismbecause religion has the power to motivate people to act. Indeed, acts ofviolence, according to these scholars, have been committed under the bannerof religion since the time immemorial. That’s why religious or sacredterrorism is said to be as old as religion itself. Several other scholars assertthat religious terrorists are largely motivated by religion but they are alsodriven by political considerations. This article tries to elaborate religious orsacred terrorism or ‘new terrorism,’ according to some scholars. The first partof this article tries to elaborate the meanings of ‘terrorism’ and ‘religion’, todefine religious terrorism, and to explain its root and trigger causes. Thesecond part tries to discuss the opinions of scholars who claim that religiousterrorism is real and not as a mere mask of other worldly interests, toelaborate the characteristics of religious terrorism, and to explain whyreligious terrorism is mostly associated with Islam.